Seroprevalence and Risk Factors of Sexually Transmitted Blood-Borne Infections among Pregnant Women Attending Antenatal Care in Jirapa, Upper West Region of Ghana - Eugene D. Kuugbee; Gloria Maaldu; Aseta Adamu; Nafisa Salia; Williams Walana; Sylvanus Kampo; Ezekiel K. Vicar; Juventus B. Ziem (Canadian Journal of Infectious Diseases and Medical Microbiology, 2023)
Background. Sexually transmitted blood-borne infections (STBBIs) contribute to negative outcomes of pregnancy. Hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), and syphilis infections in pregnancy contribute significantly to maternal and child morbidities and mortalities. This study assessed the prevalence, knowledge, and risk factors of STBBIs (HBV, HCV, HIV, and syphilis) among pregnant women attending antenatal clinics in Jirapa. Methods. A cross-sectional study design involving 246 pregnant women was employed for the study. A structured questionnaire was used to solicit information about the knowledge, prevalence, and risk factors of STBBIs. Results. The overall prevalence of STBBIs was 11.4%; HBV prevalence was 9.8% and 0.8% each for HCV, HIV, and syphilis. About 66% of mothers were aware of mother-to-child transmission of infections during pregnancy. Knowledge of transmission of HIV (93.9%), hepatitis (67.1%), and syphilis (53.7%) in pregnancy was relatively high. Knowledge of risk factors for HIV, hepatitis, and syphilis was 97.6%, 74.4%, and 76.0%, respectively. More than 98% of respondents knew about the prevention of HIV, hepatitis, and syphilis. Significant risk factors associated with and predictive of STBBIs were female genital mutilation (FGM) and gravidity. Conclusion. The occurrence of STBBIs among pregnant women was strongly associated with FGM and gravidity. Public health education should be directed at stopping the practice of FGM and improving reproductive health in the study area.